2014
DOI: 10.1103/physreve.89.052908
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization transition in networked chaotic oscillators: The viewpoint from partial synchronization

Abstract: Synchronization transition in networks of nonlocally coupled chaotic oscillators is investigated. It is found that in reaching the state of global synchronization the networks can stay in various states of partial synchronization. The stability of the partial synchronization states is analyzed by the method of eigenvalue analysis, in which the important roles of the network topological symmetry on synchronization transition are identified. Moreover, for networks possessing multiple topological symmetries, it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 55 publications
1
29
0
3
Order By: Relevance
“…Yet recent studies give the accumulating evidences which show that cluster synchronization is also observable in complex networks [17,18,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49]. The first batch of evidences come from the synchronization of small-size complex network possessing reflection symmetries [14,17,19,40,42], where it is found, in spite of the presence of random shortcut links, the oscillators can be synchronized in pairs according to the network reflection symmetries. Additional evidences from large-size complex network possessing permutation symmetries have been also provided [43][44][45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%
“…Yet recent studies give the accumulating evidences which show that cluster synchronization is also observable in complex networks [17,18,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49]. The first batch of evidences come from the synchronization of small-size complex network possessing reflection symmetries [14,17,19,40,42], where it is found, in spite of the presence of random shortcut links, the oscillators can be synchronized in pairs according to the network reflection symmetries. Additional evidences from large-size complex network possessing permutation symmetries have been also provided [43][44][45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%
“…To give deeper insights into the synchronous transition, particularly from CSO to PS as a function of ρ, we below using master stability function (MSF) [43][44][45] approach to quantitatively characterize the synchronous boundary separating these two regimes. As discussed previously, Eqs.…”
Section: B Master Stability Function Approachmentioning
confidence: 99%
“…Very recently, some of the authors and co-workers studied the desynchronous pattern of networked dynamics in detail [49,50]. We took a closer look at the nonzero time-averaged synchronization errors for each node and found that they are linearly related to the absolute value of the eigenvector element of the Laplacian matrix with the corresponding critical mode of the coupled systems.…”
Section: Introductionmentioning
confidence: 98%